National Identity and White Supremacy in Wendy Lill’s The Occupation of Heather Rose - Wang, Zengshi (Cultural Arts Research and Development, 2022)
This paper reevaluates Wendy Lill’s The Occupation of Heather Rosefrom cultural and political perspectives. The effects of the white colonization and the formation of the Natives’ authentic national identity are among the main concerns of the study. As presented in the play, white supremacy is the main reason behind thesuffering of the Natives. The study confirms the responsibility of the white race and its legacy in the dilemma of Natives in Canada. It aims to correct the misconceptions regarding the real motives behind the racist notion of white supremacy as the results not from personal discrimination or prejudices but rather racialized educational, social, political, and cultural systems that infect the whole Canadian society. Interestingly enough, Lill concentrates on the problems of the Natives through the experience of Rose the white nurse. The study helps to credit her attempts to warn against the injustices felt by the Natives and the Whites’ responsibility of them. Depending on textual analysis of the colonizers’ and colonized attitudes in the play, the researchexposes examples of the white supremacy approaches that cause harmful consequences on the Natives’ identity in Canada. Lill has chosen three Western characters to resuscitate them in her play; Alice in Wonderland, Marlowe’s Heart of Darkness, and FlorenceNightingale’s the lady with the lamp. The importance of these references is discussed in detail. The study calls for sympathy and a deep understanding of the Natives’ problems and identity. It calls for embracing the Natives as a powerful constitutive of the Canadian society.